PENGARUH SEKTOR MONETER TERHADAP STABILITAS SISTEM KEUANGAN DI INDONESIA - Sera Novella; Syofriza Syofyan (Media Ekonomi, 2018)
The Research aims to determine whether there is influence of the monetary sector on financial system stability (SKK) in Indonesia. The method used in this study is the error corrections model (ECM) method. The data used in the study are Credit, Foreign Direct Investments, Portfolio Investment and Gross Domestic Product, Net Performing Loans, Exchange Rates, Inflation and Bi Rate. The results showed that foreign direct investment instruments, net performing loans, exchange rates and inflation affect the stability of the financial system in Indonesia. Then simultaneously the four independent variables significantly influence the stability of the financial system in Indonesia in the long run. Bi rate and partially portfolio investment variables do not significantly influence the stability of the financial system in Indonesia. The policy implication of these results is that every investment that enters Indonesia must be properly signed and the capital inflow must be right on target and directly distributed to the projects to be built or to the intended industry, so there is no excess liquidity in the banking